Web-Based Geographic Information System (GIS) for Mapping Senior High Schools in Muara Enim Regency - Azka Kurniasti (Institute of Information Technology and Social Science (IITSS), 2024)
Muara Enim Regency, located in South Sumatra Province, faces challenges in managing and disseminating data related to Senior High Schools (SMA). The local Department of Education still performs data management manually, leading to inefficiencies, delays, and frequent errors. Additionally, limited access to comprehensive information regarding school locations and profiles results in unequal distribution of student enrollment across schools. This study develops a Web-Based Geographic Information System (GIS) designed to map Senior High Schools in Muara Enim Regency. The system was built using the Web Engineering methodology, with HTML and PHP for development and MySQL as the database management system. The GIS platform enables the Department of Education to record, manage, and analyze school data efficiently, while also allowing the public particularly parents and prospective students to easily search for and view accurate school information and geographical locations.